"You can always adopt": What clinic staff need to know about adoption and fostering?. (March 2013) - Balen, Rachel
Abstract This paper presents information and research about adoption and fostering, and explains some of the relevant processes. In order that those providing infertility services can play an informed, supportive and empowering role in the decision-making of those whose infertility treatment has been unsuccessful, a number of issues are highlighted. These include the changing profile of children awaiting adoption and fostering; ongoing contact between children and their birth families; the adoption of children from abroad; moving from infertility treatment to adoption or fostering; and the potential ongoing impact of infertility and failed treatment.